PSYCHOLOGICAL STATUS INFLUENCE ON THE INTIMA-MEDIA COMPLEX THICKNESS AND TUMOR NECROSIS FACTOR-ALPHA IN YOUNG MEN 18–25 YEARS OLD - Bilovol, O.M.; Kniazkova, I.I.; Mishchenko, V.M.; Barbashova, V.O.; Kuzminova, N.V.; Kryvoshapka, О.V.; Abramova, L.P. (World of Medicine and Biology, 2024)
The purpose of the study was to investigate the influence of psycho-emotional status on carotid artery wall characteristics, plasma levels of C-reactive protein and tumor necrosis factor-alpha in men aged 18–25 years. We examined 65 young men (average age 21.9±2.3 years) without cardiovascular pathology and any somatic diseases in the anamnesis. According to the psycho-emotional state (The Spielberger State-Trait Anxiety Inventory), the examined men were divided into 2 groups: main – with high anxiety – 35 people and the control group – 30 people (average age 21.3±2.1 years) without violations of psycho-emotional status. It was found that in the main group there was an increase of carotid intima-media thickness, changes in carotid arterial elasticity according to elasticity and distensibility coefficients, Peterson’s and Young’s modules in comparison with the control group. It was established that in young aged with high levels of anxiety, an increase in the content of C-reactive protein and tumor necrosis factor-α in blood serum is determined in comparison with the group without psycho-emotional status disorders.
Keywords: young men; psycho-emotional disorders; elasticity of arterial wall; tumor necrosis factor-alpha; C-reactive protein